Study on the spatial and temporal evolution of ecosystem service value based on land use change in Xi’an City - Lei Han; Yan Li; Zhemin Ge; Fang Fang; Lan Gao; Jin Zhang; Zhen Du; Liping Cui (Scientific Reports)
Abstract Ecosystem service value (ESV) is essential for understanding regional ecological benefits and resources. This study utilizes the fourth phase of land use data from the Resource and Environment Science Data Centre of the Chinese Academy of Sciences. We corrected the ESV coefficient using the equivalent factor method for value per unit area and integrated the biomass factor of farmland ecosystems in Shaanxi Province. This allowed us to adjust the equivalent factor for China’s terrestrial ecosystem on a geographic scale. Based on these corrections, we analyzed changes in land use and the evolution of ecosystem service value over the past two decades in Xi’an, China. Our findings indicate that the proportions of cultivated and forest land in Xi’an remained stable from 2000 to 2020, despite an increase in construction land and a decrease in cultivated areas. Forest and unused lands remained stable, while grassland and water bodies fluctuated. The ESV related to land use in Xi’an increased by 938.8 million yuan during this period, with high-value areas primarily located in the forested regions south of the Qinling Mountains and along the Weihe, Bahe, and Chanhe Rivers. Low–value zones were concentrated in the urban core. This research enhances methodologies for quantifying urban ESV, providing vital support for land resource management, ecological conservation, and high-quality urban development in major cities in China. These findings will inform policy-making for sustainable urban growth.